![(2,-3)\text{ ;(3,-3)}](https://img.qammunity.org/2023/formulas/mathematics/college/e0md85hn7mgu2k6s3waxynooosv2o7v5o1.png)
Step-by-step explanation
Step 1
![\begin{gathered} f(x)=x^2-5x+3 \\ f(x)=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dewzp8n1t81xe8zu2uhzn9eyv3z075a2ok.png)
there is a value for y, that is the same for both equations, so
![\begin{gathered} y_1=y_2 \\ x^2-5x+3=-3\Rightarrow equation\text{ (3)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jduax368dgpohckohootug4r7icuampcf7.png)
solve equation (3)
![\begin{gathered} x^2-5x+3=-3 \\ \text{add 3 in both sides} \\ x^2-5x+3+3=-3+3 \\ x^2-5x+6=0 \\ x^2-5x+6=0\Rightarrow ax^2+bx+c=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6ors5ns6y8ewcdgspicaa51sods3sks2ra.png)
hence, we can use the quadratic formula
![\begin{gathered} x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ \text{replace} \\ x=\frac{+5\pm\sqrt[]{(-5)^2-4\cdot1\cdot6}}{2\cdot1} \\ x=\frac{+5\pm\sqrt[]{25-24}}{2} \\ x=\frac{+5\pm\sqrt[]{1}}{2} \\ x=(+5\pm1)/(2) \\ x_1=(5+1)/(2)=(6)/(2)=3 \\ x_2=(5-1)/(2)=(4)/(2)=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/km16gbfer3z9x3jlxwqyl0tc9nbjvel7hk.png)
so, we have 2 values for x ( 2 and 3)
Step 2
now, find the images
a) when x= 3
![\begin{gathered} f(x)=x^2-5x+3 \\ f(x)=(3)^2-5(3)+3 \\ f(x)=9-15+3 \\ f(x)=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mb1hojte61b3qeaba2jct67opxtefjb5dj.png)
b) when x= 2
![\begin{gathered} f(x)=x^2-5x+3 \\ f(x)=2^2-5\cdot2+3 \\ f(x)=4-10+3 \\ f(x)=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ignk1ils14qfv3e1xqysfijrq1uolba7ka.png)
therefore the solutions are
![\begin{gathered} (2,-3)\text{ ;(3,-3)} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jzzx53b9sct56eaewuyhegpx94kpxf5dx1.png)
I hope this helps you